Effectiveness of slow deep breathing exercise on decreasing stress levels for patients with diabetes mellitus - Warsono Warsono; Arief Yanto (South East Asia Nursing Research, 2020)
The prevalence of diabetes mellitus patients increases in Semarang province every year. Whereas, it reached 120 numbers of patients in Kedungmundu public health center by 2020. One of the psychological problems encountered by patients with diabetes is a high risk of stress levels.  The condition of stress, anxiety, and fear influence the production of adrenaline hormones which aggravate the capability of patients to perform daily living activities. Slow deep breathing exercise is a nonpharmacologic method to reduce stress levels on diabetes mellitus patients.  This study aimed to investigate the effect of slow deep breathing exercises on decreasing stress levels for patients with diabetes mellitus. This study used a quasi-experiment pretest-posttest with a control group design was conducted at Kedungmundu public health center, Semarang. All of 32 samples were recruited in this study. Wilcoxon test analysis calculated a value of p=0.000 < ɑ 0,005. The statistical analysis found significantly different results between the pretest and posttest in the experimental group. Slow deep breathing exercise is effective to decrease the stress levels for patients with diabetes mellitus. Slow deep breathing exercise is strongly suggested for patients with diabetes mellitus as self-intervention to reduce stress levels.